Teaching methodologies in remote teaching in the pandemic contexto 2020-2021 (Research, Society and Development, 2023)
This work describes the experience of an observation of a refletive nature carried out at the Álvaro Maia state school, presents a clipping of the reality of the research that is being developed in the Graduate Program in Science and Humanities Teaching (PPGECH) of the Federal University of Amazonas – Institute of Agriculture and Environment Education (UFAM - IEAA) which is also one of the  sections of the dissertation that analyzed the methodologies used during remote teaching in the context of the coronavirus (COVID-19) 2020-2021, our objective was to meke a comparison between the traditional teaching methodologies that the school used and the active teaching methodologies necessary for this teaching model. For this purpose, a participatory research approach was used since the author would be inserted within the context of the research, in his own work environment and the observation technique was chosen, which would be the appropriate data collection instrument for the research. Reviewing the literature, the overview provided the necessary foundation fore the discussion of ideas and critical analysis of the observed data and it was possible to see the great contrast between the use of methodologies during the period of remote teaching in this school.